STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN COFFE DI GHONA COFFE KOTA JAMBI (Jurnal Riset Manajemen dan Akuntansi, 2023)
This thesis aims to find out how marketing is to increase coffee sales at Ghona Coffee Jambi City. This study uses a qualitative approach by using the results of interviews and accurate data sources. From the results of research that has been carried out by researchers, in this case the following conclusions can be drawn: (1) The marketing strategy to increase sales at Ghona Coffee is dominantly using the 4 p marketing mix which includes product, price, promotion, and location or place . The products used at Ghona Coffee always prioritize the quality of goods and services.The price set at GhonaCoffe is fairly economical, friendly in the pocket, right for students and can be reached by all people. Promotions are carried out at GhonaCoffe by disseminating information about GhonaCoffe because more customers will affect sales levels and increase sales at GhonaCoffe. And as for the implementation of the location strategy carried out at Ghona Coffee, it can be said that it meets the criteria.(2) There are two obstacles in increasing the sales of GhonaCoffe regarding the product and also the location. Where the food products offered at Ghona Coffee can be said to be minimal in food products, while the location of Ghona Coffee is very narrow for parking vehicles.(3) GhonaCoffe's efforts in increasing sales are twofold, namely products and locations where GhonaCoffe's products will provide the best and also meet consumer demand, and GhonnaCoffe will provide a good parking space for vehicles.